Compreensão leitora de palavras e frases: elaboração de procedimento avaliativo - Oliveira, Adriana Marques De [UNESP] (2013)
This study aimed to develop procedures for assessing reading comprehension of words and phrases and characterize the performance of students of 2nd year of elementary school in this procedure. It was divided into two phases: 1) preparation of evaluation tests of reading comprehension, consisting of three events: comprehension of written word (CWW), sentences (CWS) and sentences through pictures (CSP) and 2) application of the elaborated evaluation in 120 students distributed in the following groups: GI, 60 students from a public (municipal) school and GII, 60 students from a private school. The CWW test obtained the highest average of score, followed by CSP and CWS for both groups, since the picture contributes to the comprehension of the meaning either of the word and sentences. The procedure was effective to assess initial skills of reading comprehension once it identified inherent difficulties related to the literacy process.